Salivary parameters and oral health status amongst adolescents in Mexico - A. E. González-Aragón Pineda; A. García Pérez; F. García-Godoy (BMC, 2020)
Abstract Background In the last years an increased interest in the use of salivary parameters in connection with caries experience and caries prediction has been shown. In schoolchildren investigations are known, where the relationship between caries prevalence and salivary parameters has been assessed, but in the adolescent population studies are scarce. The aim of the study was evaluate of the association among salivary parameters, oral health status and caries experience in adolescents in Mexico. Methods A cross-sectional study was conducted on 256 (DMFT≥5) and 165 (DMFT< 5) 12-to- 14-year-old adolescents. From all the adolescents, unstimulated mid-morning saliva samples were collected, after which the salivary flow rate was calculated, and the salivary pH and buffer capacity was measured. The caries was evaluated via the application of the DMFT score. Clinical variables such as oral hygiene and dental calculus were examined in the adolescent's oral cavity. The adolescents provided data on their personal characteristics by completing a questionnaire, while socioeconomic data were collected from their parents. Descriptive, bivariate and logistic regression model analyses were performed. Results The prevalence of caries was 61.1% (DMFT≥5) in permanent dentition, with 72.7% of subjects presenting poor oral hygiene. The mean levels of salivary flow rate, pH, and buffer capacity was significantly lower (p < 0.05) in adolescents with caries score of DMFT≥5 than in those with caries score of DMFT < 5. Salivary flow and buffer capacity were higher in boys than in girls. The logistic regression model applied showed that adolescents with a salivary flow rate < 1 ml per min were more likely to present caries [OR = 1.58 (CI95% 1.04-2.40); p = 0.033] than adolescents with a flow rate ≥ 1 ml per-min, and that, for each unit of increased pH, the probability of presenting caries reduced by 76% [OR = 0.24 (CI95% 0.10-0.55); p = 0.001]. Conclusion Significant association was found in salivary flow rate, pH and buffer capacity in adolescents with caries (DMFT≥5). In addition to differences of these parameters by sex, the results suggest saliva parameters may act as indicators of caries in adolescents.